Perceived Employabillity: Peranan Career Calling dan Strategi Karir Sebagai Mediator - Diyah Arini Lestari; Erika Setyanti Kusumaputri (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2017)
This study aims to determine the relationship between career calling andperceived employability through career strategies as mediator on professional workers in Yogyakarta. Participants in this study are professional workers totaling 48 workers (N=48). Perceived employability scale, career calling scale and career strategy scale were used for data collection. Path analysis with bootstrapping techniques were used to analyze the data. The results of path analysis showed there is a direct influence of career calling on perceived employability without going through career strategy . Keywords: career calling, perceived employability, career strategies